Advocating Women’s Rights in the Italian Periodical Press: Lidia Poët (1855–1949) and Teresa Labriola (1871–1941) - Batsleer, Eline (Quaderni d'Italianistica)

(untitled) (Iter Press, 2023)
Lidia Poët (1855–1949) and Teresa Labriola (1871–1941) were two pioneers of the fight for women’s rights in Italy. Despite being among the very first Italian women to graduate from the Faculty of Law at the University of Rome and the University of Torino, respectively, they were inescapably limited in the pursuit of professional careers. Inspired by their own personal experiences, both women started openly questioning the restricting values of patriarchal society and the lack of legal and political rights for women in their essays and conference presentations. Not only did they fight their individual battles by triggering public debate, but they also considered it their crucial task to create more awareness among the broader female population. Given the fact that the late nineteenth to early twentieth century was a particularly flourishing time for the periodical press, it is not surprising that both Poët and Labriola soon discovered the endless possibilities of magazines and newspapers. The aim of this essay is to illustrate how these two women turned to the periodical press and used it as a weapon in their quest for women’s legal rights. In addition, it explores the development of a nationalist feminism that emerged from their wartime writings.